A case study of packaging waste collection systems in Portugal – Part II: Environmental and economic analysis. (March 2017) - Pires, Ana; Sargedas, João; Miguel, Mécia; Pina, Joaquim; Martinho, Graça
Highlights: Mixed and bring packaging waste collection were compared by environmental and economic aspects. Life cycle assessment and economic indicators were used. Bring collection is in general performing better in both analysis. Curbside in mixed system needs to be improved before being dismissed. Abstract: An understanding of the environmental impacts and costs related to waste collection is needed to ensure that existing waste collection schemes are the most appropriate with regard to both environment and cost. This paper is Part II of a three-part study of a mixed packaging waste collection system (curbside plus bring collection). Here, the mixed collection system is compared to an exclusive curbside system and an exclusive bring system. The scenarios were assessed using life cycle assessment and an assessment of costs to the waste management company. The analysis focuses on the collection itself so as to be relevant to waste managers and decision-makers who are involved only in this step of the packaging life cycle. The results show that the bring system has lower environmental impacts and lower economic costs, and is capable of reducing the environmental impacts of the mixed system. However, a sensitivity analysis shows that these results could differ if the curbside collection were to be optimized. From economic and environmental perspectives, the mixed system has few advantages.